The solution to the Feldstein-Horioka puzzle - Charles Horioka; Nicholas Ford (Osaka University, Institute of Social and Economic Research (ISER), 2017)
The purpose of this paper is to set out a surprisingly simple solution to the Feldstein-Horioka Puzzle or Paradox, which is that even though global financial markets appear to be integrated, levels of saving and investment are correlated across countries because financial markets cannot, by themselves, achieve net transfers of financial capital. This is because net transfers of financial capital require the integration not only of financial markets but also of goods markets and because there are substantial frictions in goods markets (e.g., transport, marketing, and distribution costs, technical standards, certification procedures, tariffs and nontariff barriers, etc.).
Keywords: F15; F21; F32; F36; G15; 330; Capital flows; capital mobility; capital transfers; Feldstein-Horioka Paradox; Feldstein-Horioka Puzzle; financial market integration; goods market integration; interest rate parity; international capital flows; international capital mobility; investment; net capital transfers; Niehans model; real interest rate parity; saving; saving-investment correlations; trade frictions